2022
DOI: 10.1111/1911-3846.12742
|View full text |Cite
|
Sign up to set email alerts
|

The SEC Filing Review Process: A Survey and Future Research Opportunities*

Abstract: As part of its goal to monitor and enhance the quality of information available to investors, the SEC reviews companies' filings to ensure compliance with applicable financial reporting and disclosure requirements. Increased public interest and the substantial costs for both the SEC in reviewing and the companies in responding have led to a rapidly growing body of accounting literature that examines the filing review process. We survey and comment on 80 published and unpublished academic research papers in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 114 publications
(233 reference statements)
1
14
0
Order By: Relevance
“…Under section 408 of the Sarbanes‐Oxley Act of 2002 (SOX), 2 the SEC is required to review firms' periodic filings at least once every three years. Cunningham and Leidner (2022) document, however, that the SEC does so more often, reviewing nearly half of the firms in any given year. The DCF selectively reviews filings based on specific criteria identified in SOX as well as any other criteria the SEC determines to be important 3 .…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Under section 408 of the Sarbanes‐Oxley Act of 2002 (SOX), 2 the SEC is required to review firms' periodic filings at least once every three years. Cunningham and Leidner (2022) document, however, that the SEC does so more often, reviewing nearly half of the firms in any given year. The DCF selectively reviews filings based on specific criteria identified in SOX as well as any other criteria the SEC determines to be important 3 .…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The SEC sends comment letters about various issues, including those that do not constitute serious accounting violations requiring restatements (Johnston and Petacchi 2017; Cassell et al 2013; Cunningham and Leidner 2022). If a firm's accounting deviations, regardless of severity, become more noticeable when compared to those of its peers that have similar accounting systems, then higher financial statement comparability might lead to an overall increase in comment letter issuance with no corresponding increase in the discovery of serious accounting issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulatory oversight is an important mechanism that has a deterrence effect and influences firms' reporting decisions. (Cunningham and Leidner 2022). This review is done by filing review offices at the DCF, where the offices are organized by industry.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
“…See a recent review about studies on the SEC filing review process inCunningham and Leidner (2022) 13 It is not easy to define post-period if there is more than one change. Also, the sample size of firms that experiences more than one change is small.…”
mentioning
confidence: 99%